Determination of optimum planting time of different Sesame (Sesamum indicium L.) varieties for Chewaka district, Western Oromia, Ethiopia - Chala Debela; Alemayehu Dabesa; Tadese Birhanu; Teshome Gutu; Feyera Tekele (Open Journal of Plant Science - Peertechz Publications, 2023)
Sowing date is the major problem in the production and productivity of sesame in western Oromia Ethiopia. The experiment was conducted to identify optimum sowing dates for sesame varieties to produce better seed yields. A field experiment consisting of the combination of three sesame varieties and three sowing times employed Randomized Complete Block in factorial arrangements with three replications. Analysis of variance indicated that plant height; branches number per plant and number of capsules per plant were significantly increased with sowing sesame at the onset of rainfall. All sesame varieties sown on the onset of rainfall gave the maximum seed yield in both years whereas three varieties had low yield at 10 days after the first and 20 days after the first. Among the three varieties, the Walin variety produced a maximum seed yield of 670 and 747 kg ha-1 on a farm in the first and second year respectively. The maximum yield (670 and 971 kg ha-1) was obtained from Walin and Obsa sesame varieties in the first and second years of the farm respectively. Therefore, the result indicated that sowing sesame varieties at the onset of rainfall is recommended for Chewaka areas and similar agroecology.